Análise da fadiga muscular localizada em atletas e sedentários através de parâmetros de freqüência do sinal eletromiográfico - Santos, Marcelo Cláudio Amaral [UNIFESP] (2008)
Though the analysis in the frequency domain of the Electromyographic Signal (EMG) was used in the characterization of the localized muscular fatigue process their application, specifically the Median Frequency (MF), is rarely explored in the sports. The objective of this study was to verify the viability in the application of the EMG signal, through of the frequency domain analysis, as parameter for determination and differentiation of the behavior of located muscle fatigue. Two groups of subjects one characterized as athletes (n=12) and other as sedentary (n=12), were submitted to analysis based in procedures executed in three different experimental situations, all involving the isometric exercise modality: i) maximum test for determination of the Maximum Voluntary Isometric Contraction (MVIC); ii) fatigue test, 35 sec. sustained load of 80% of MVIC; iii) recovery test, 10 sec. sustained load of 80% of MVIC; where was monitored the behavior of MF in the first three (Fmedi) and last three seconds (Fmedf) of the EMG signal of anterior tibial muscle during the fatigue test. During the 10 seconds of the recovery test MF was calculated regarding the whole period (Fmedr) this parameter was used to calculate the Recuperation Muscle Index (RMI). The results showed that Fmedf presented a low value in relation to Fmedi in both groups (p <0.05). Also the value of Fmedi and Fmedf for the athlete group presented larger higher value in comparison with the sedentary group (p <0.05). The mean value and standard deviation of RMI for the athlete group were 62.1% ±28.7 and for sedentary group was 55.2% ±27.8 (p>0.05). In general terms the results presented in this study allow inferring the viability in the application of the frequency domain parameters of the EMG signal for the determination and differentiation of the located muscle fatigue behavior.